2020
DOI: 10.4012/dmj.2019-223
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hydrolysis degradation of silane coupling agents on mechanical performance of CAD/CAM resin composites: <i>In silico</i> multi-scale analysis

Abstract: The aim of this study was to build an in silico computer-aided design and computer-aided manufacturing (CAD/CAM) resincomposite-block (RCB) model with different silane coupling ratios and to evaluate the physical and mechanical properties of the models, including the elastic modulus, Poisson's ratio, compressive strength, and maximum principal strain. Nanoscale CAD/CAM RCB models were designed by using CAD software that consisted of twelve spherical silica nanofiller particles and a resin matrix. Seven nanosca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…The actual degree of conversion of the bonding agent between the filler and matrix is less than the ideal condition [30]. When the silane coupling ratios of the filler decrease, the maximum MPS value distribution moves to the matrix/filler interface where the silane coupling layer is located [31]. Within the limitation of the in silico static multiscale analysis used in this study, the area where the maximum MPS value was observed in the SS silica filler micro-scale model increased around the filler compared with the RC containing IS filler, suggesting that a crack in a RC containing SS filler may more easily propagate than in a RC containing IS filler.…”
Section: Discussionmentioning
confidence: 95%
“…The actual degree of conversion of the bonding agent between the filler and matrix is less than the ideal condition [30]. When the silane coupling ratios of the filler decrease, the maximum MPS value distribution moves to the matrix/filler interface where the silane coupling layer is located [31]. Within the limitation of the in silico static multiscale analysis used in this study, the area where the maximum MPS value was observed in the SS silica filler micro-scale model increased around the filler compared with the RC containing IS filler, suggesting that a crack in a RC containing SS filler may more easily propagate than in a RC containing IS filler.…”
Section: Discussionmentioning
confidence: 95%
“…The F1s peak in the XPS spectrum and the greater atomic percentage in the after-immersion group than the before-immersion group suggest that hydrolysis in the silane coupling layer occurred during water immersion. Although it has been reported that XPS analysis can be used to qualitatively assess the target atom [40][41][42], in the case of CAD/CAM resin composites, hydroxyl groups develop on the silane coupling layer as well as on the surface of the fillers. Therefore, assessing the absolute amount of the hydrolyzed silane coupling layer is impractical.…”
Section: Discussionmentioning
confidence: 99%
“…15,16,19,20 Aging of composite resins in water results in release of filler particles from the matrix due to the hydrolytic degradation of silane coupling agent and fatigue crack propagation. [21][22][23] Grafting of hydrophobic polymer chains to the filler surface decreases water sorption at the interface and improves interface durability due to the hydrophobicity of the coupling layer. Moreover, it further stabilizes the filler-matrix interface by chemical and loose bridging.…”
Section: Introductionmentioning
confidence: 99%